Meta-Interpretatif Perilaku Seksual Transgresif Remaja dari WhatsApp Group Pornografi - Al Mukhollis Siagian (Jurnal Pembangunan Nagari, 2023)
ABSTRACT The study aimed to analyze changes in sexual behavior and the prevalence of risk of transgressive sexual behavior from the consumption of organized online pornography in WhatsApp Groups (WAG) for young peoples. The research method used is qualitative interpretive three approaches; Literature review of relevant studies from 2010, interviews, and methods of expertise. The results found 4,210 young peoples experienced pornography addiction and changes in sexual behavior. They are spread in 10 Pornography WAGs with a total of 15 admin accounts. The age range of young peoples in the Pornography WAG is 14 years to 22 years, males numbering 52.49% and females as many as 47.51%. The education status of Junior High School is 13.87%, in Senior High Shool is 48.17% and in Universities as many as 37.96%. The most normal young peoples sexual behaviors include; kissing the forehead/cheek of the opposite sex, hugging, kissing lips, masturbation, fantasizing, touching sensitive parts of the opposite sex, petting, neckingand intercourse. While young peoples at a high stage of pornography addiction show transgressive sexual behavior entering criminal acts homosexual, bisexual, sadism, sodomy and prostitution. It was concluded that young peoples who joined the Pornography WAG had made sexual behavior a daily necessity and the Pornography WAG had the potential to expand acts of sexual harassment, rape, homosexuality, bisexuality, sadism, and sodomy. Therefore, preventive-curative, educative-productive and solutive-constructive intervention policies are needed from stakeholders.